Synthesis Of ZnO Nanomaterials, WOx Nanoparticles And WOx/ZnO Nanocomposites For Inhibition Of Bacterial Growth And Organic Dyes Removal - Ying, Yuet Lee (2018)
Waste water treatment using wide bandgap semiconductor particles, in particular the ZnO nanoparticles, is one of the alternative and economical approach. However, the photodegradation of organic pollutants by ZnO nanoparticles is relatively poor due to fast recombination of photogenerated electron-holes. In addition, the antibacterial activities reported from various research groups were often confusing and contradicting. The present study aimed to improve the photocatalytic performance of ZnO nanoparticles from the morphology and coupling perspectives. In this project, the ZnO submicron rods (46.19 %) demonstrated better photodegradation efficiency than ZnO nanodisks (21.47 %) after 75 minutes of ultraviolet light irradiation. The photodegradation efficiency of ZnO submicron rods was improved slightly by depositing narrow bandgap semiconductor (WOx nanoparticles). The photodegradation efficiency of WOx/ZnO nanocomposites achieved 48.38 % under UV irradiation. These nanoparticles were tested for their antibacterial activity using antibacterial susceptibility assay without and with UV light irradiation. Based on the results, both ZnO submicron rods and WOx/ZnO nanocomposites displayed better antibacterial performance against Gram-positive bacteria (Bacillus subtilis and Staphylococcus aureus) than Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), the effectiveness of inhibition on bacteria by these particles were bacteria-type dependent, and only Escherichia coli was sensitive to the presence of WO3.